2012
DOI: 10.1016/j.leukres.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Directed therapy for patients with myelodysplastic syndromes (MDS) by suppression of cyclin D1 with ON 01910.Na

Abstract: Background We previously demonstrated upregulation of c-myc, survivin, and cyclin D1 in CD34+ bone marrow mononuclear cells (BMMNCs) of patients with trisomy 8 and monosomy 7 myelodysplastic syndromes (MDS). “Knockdown” of cyclin D1 by RNA interference decreased trisomy 8 cell growth, suggesting that this might be a therapeutic target in MDS. Experimental Design We performed preclinical studies using BMMNCs from patients with MDS and AML to examine the effects of the styryl sulfone ON 01910.Na on cyclin D1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…These findings support the notion that p38MAPK inhibitors along with other currently investigational approaches, namely the multi-kinase and SMAD2/3 signaling inhibitors, may prove beneficial for MDS-related AIMs. Rigosertib, a multi-kinase inhibitor that targets PI3 kinase, displayed clinical efficacy in MDS patients with increased blast counts, culminating in a substantial reduction of blastic population, hematologic improvement and extended overall survival periods [68,69]. The SMAD2/3 inhibitor has already shown erythropoietic activity in cancer patients and healthy volunteers and is being evaluated in MDS-associated anemia [70].…”
Section: Five-year Viewmentioning
confidence: 99%
“…These findings support the notion that p38MAPK inhibitors along with other currently investigational approaches, namely the multi-kinase and SMAD2/3 signaling inhibitors, may prove beneficial for MDS-related AIMs. Rigosertib, a multi-kinase inhibitor that targets PI3 kinase, displayed clinical efficacy in MDS patients with increased blast counts, culminating in a substantial reduction of blastic population, hematologic improvement and extended overall survival periods [68,69]. The SMAD2/3 inhibitor has already shown erythropoietic activity in cancer patients and healthy volunteers and is being evaluated in MDS-associated anemia [70].…”
Section: Five-year Viewmentioning
confidence: 99%
“…The relative selective toxicity of rigosertib to malignant but not to nonmalignant normal hematopoietic cells was demonstrated dramatically in patients with MDS (49). The in vitro treatment with rigosertib of malignant blasts from patients with MDS decreased their numbers as measured by CD34 + and CD33 + bone marrow precursors, as well as measurement of Trisomy 8 (49).…”
Section: Rigosertib’s Mechanism Of Action and Anti-cancer Activitymentioning
confidence: 99%
“…The in vitro treatment with rigosertib of malignant blasts from patients with MDS decreased their numbers as measured by CD34 + and CD33 + bone marrow precursors, as well as measurement of Trisomy 8 (49). In contrast, normal human bone marrow progenitors exhibited markedly reduced toxicity to rigosertib (,50).…”
Section: Rigosertib’s Mechanism Of Action and Anti-cancer Activitymentioning
confidence: 99%
“…6 First-in-man studies of rigosertib in solid tumors demonstrated excellent tolerability with limited hematologic toxicity. 7 Rigosertib has also demonstrated pre-clinical and early clinical activity in myelodysplastic syndromes (MDS) 8,9 and it is currently being tested in a randomized phase III trial in patients with relapsed/refractory MDS [NCT01241500].…”
mentioning
confidence: 99%